2015
DOI: 10.1007/s11099-015-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium chloride stress on gas exchange, chlorophyll content and nutrient concentrations of nine citrus rootstocks

Abstract: We investigated the influence of salinity (0, 25, 50, or 75 mM NaCl) on gas exchange and physiological characteristics of nine citrus rootstocks (Cleopatra mandarin, Carrizo citrange, Macrophylla, Iranian mandarin Bakraii, Rangpur lime, Rough lemon, Sour orange, Swingle citrumelo, and Trifoliate orange) in a greenhouse experiment. Total plant dry mass, total chlorophyll (Chl) content, and gas-exchange variables, such as net photosynthetic rate (P N ), stomatal conductance (g s ), intercellular CO 2 concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 33 publications
(35 reference statements)
1
16
0
1
Order By: Relevance
“…P N decline is a general response of plants to salinity stress mostly due to membrane damage and stomatal closure (Marín-Guirao et al 2011;Ge et al 2014;Khoshbakht et al 2015). In our study, potted alfalfa in the controlling experiment showed declining P N with an increase of salinity level.…”
Section: Photosynthesis Transpiration and Wuementioning
confidence: 46%
See 1 more Smart Citation
“…P N decline is a general response of plants to salinity stress mostly due to membrane damage and stomatal closure (Marín-Guirao et al 2011;Ge et al 2014;Khoshbakht et al 2015). In our study, potted alfalfa in the controlling experiment showed declining P N with an increase of salinity level.…”
Section: Photosynthesis Transpiration and Wuementioning
confidence: 46%
“…Additionally, this trend not only occurred during the response of fine root morphology to saline gradient described above, but also implied a key mechanism for depressed photosynthetic inland-alfalfa performance in the future. With the increase of salinity stress, T r decline is a common response of juvenile plants among a wide range of species, such as Phoenix dactylifera L. (Youssef and Awas 2008), citrus (Khoshbakht et al 2015), Sarcocornia fruticosa (L.) A.J. Scott (Redondo-Gómez et al 2006), and Arundo donax L. (Nackley and Kim 2015).…”
Section: Photosynthesis Transpiration and Wuementioning
confidence: 99%
“…Khoshbakht et al [41] reported that the effects of salinity on photosynthesis range from the restriction of CO 2 diffusion into the chloroplast, via limitations on stomatal opening mediated by shoot-and root-generated hormones, and on the mesophyll transport of CO 2 , to alterations in leaf photochemistry and carbon metabolism. The authors conducted a study and investigated the NaCl effects on gas exchange parameters of nine citrus rootstocks and reported that sour orange and Cleopatra mandarin were the rootstocks most tolerant to salinity of all the nine citrus rootstocks studied.…”
Section: Salinitymentioning
confidence: 99%
“…It is generally believed that salt stress causes a decrease in chlorophyl content (Khoshbakht, Ramin & Baninasab, 2015;Qiu et al, 2017). Some reports have, however, shown an increase in chlorophyl content for a few plant species under salt stress (Stefanov et al, 2016;Shah, Houborg & McCabe, 2017).…”
Section: Discussionmentioning
confidence: 99%